2012
DOI: 10.1007/s00280-012-1897-8
|View full text |Cite
|
Sign up to set email alerts
|

The minimal impact of food on the pharmacokinetics of ridaforolimus

Abstract: Increases in ridaforolimus exposure following both the light and high-fat breakfasts were not considered to be clinically meaningful. Ridaforolimus was generally well tolerated, and there were no discontinuations due to drug-related AEs. Ridaforolimus should be given without regard to food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…At therapeutic dose levels, plasma ridaforolimus levels are commonly at or near the limit of assay detection (lower limit of quantitation, LLOQ) for the plasma assay was 0.1 ng/mL); accordingly, whole blood pharmacokinetic (PK) parameters are provided for ridaforolimus. Since the proportion of ridaforolimus in plasma relative to whole blood is influenced by the saturable binding event, there are correspondingly less than proportional increases in whole blood exposure with dose, especially above the investigated Phase III 40 mg oral dose level (NCT00538239) . The apparent whole blood terminal elimination half‐life (t 1/2 ) is approximately 56 hours, and steady‐state trough levels are generally approached after administration of 5 consecutive daily doses (q.d.…”
mentioning
confidence: 99%
“…At therapeutic dose levels, plasma ridaforolimus levels are commonly at or near the limit of assay detection (lower limit of quantitation, LLOQ) for the plasma assay was 0.1 ng/mL); accordingly, whole blood pharmacokinetic (PK) parameters are provided for ridaforolimus. Since the proportion of ridaforolimus in plasma relative to whole blood is influenced by the saturable binding event, there are correspondingly less than proportional increases in whole blood exposure with dose, especially above the investigated Phase III 40 mg oral dose level (NCT00538239) . The apparent whole blood terminal elimination half‐life (t 1/2 ) is approximately 56 hours, and steady‐state trough levels are generally approached after administration of 5 consecutive daily doses (q.d.…”
mentioning
confidence: 99%
“…The drugs used in DES target cell growth and neo-intimal proliferation to prevent in-stent restenosis and are also used for certain oncology and immunosuppression indications. 11 , 12 The effect of these potent long-acting drugs on the breastfeeding infant was a concern. The effects of antiproliferative drugs used in these stents have, to the best of our knowledge, not been studied in lactating mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently confirmed the safety and tolerability of ridaforolimus in patients. Notably, a single 40 mg dose of ridaforolimus was well tolerated in healthy adult males (Stroh et al, 2012a), and it exhibited consistent absorption rates regardless of whether it was administered with a light or high-fat breakfast. Furthermore, ridaforolimus did not prolong the corrected QT interval (QTc) in patients with advanced cancer (Lush et al, 2012).…”
Section: Introductionmentioning
confidence: 98%